2016
DOI: 10.1007/s00330-016-4212-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear wave velocities on ultrasound elastography between different machines, transducers, and acquisition depths: a phantom study

Abstract: • The shear wave velocities (SWVs) are different between different ultrasound elastography machines • The SWVs are also different between different transducers and acquisition depths • Caution is needed when using the cutoff SWVs measured under different conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
110
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 29 publications
19
110
2
Order By: Relevance
“…Histologically, IM shows perivascular and/or perimysial and/or endomysial infiltration of inflammatory cells, often associated with perifascicular atrophy or microinfarcts. 22 The results of our study are in agreement with those of previous studies, which have shown that inflammatory lesions of the pancreas, bowel and uterus have relatively high SR. 20,23,24 Although the target organs were different in our study, there were similar histologic features. Chronic pancreatitis is characterized by pancreatic infiltration of inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
“…Histologically, IM shows perivascular and/or perimysial and/or endomysial infiltration of inflammatory cells, often associated with perifascicular atrophy or microinfarcts. 22 The results of our study are in agreement with those of previous studies, which have shown that inflammatory lesions of the pancreas, bowel and uterus have relatively high SR. 20,23,24 Although the target organs were different in our study, there were similar histologic features. Chronic pancreatitis is characterized by pancreatic infiltration of inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
“…These tasks could be faced by many clinical imaging physicists nowadays. Systemic differences were shown among different transducers and vendors, which were similarly observed in the literature 18, 21, 22…”
Section: Discussionsupporting
confidence: 79%
“…They postulate that the difference between the probes might be due to the fact that the number of elements and channels differs between both transducers and that the beam profile is shaped slightly different over depth. Shin et al showed that differences between pSWE vs. Supersonic shear imaging (SSI)™ values (Aixplorer ultrasound system, SuperSonic Imagine, Aix-en-Provence, France) depended not only on the transducers but also on US machines from different vendors (e.g., with different F-number and the frame rate of imaging) [22]. pSWE values assessed in our elasticity phantom study with the Method 3 (Epiq7, C5-1 convex probe) were slightly higher than those recorded with Methods 1 and 2 (Acuson S3000, 9L4 linear probe and 4C1 convex probe.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the measurement procedure in the second part of the study was repeated five times for each target type, with the stiffness value defined as the mean of the five measurements for each ROI diameter (diameters: 40, 38, 36, 34,32,30,28,26,24,22,20,18,16,14,12,10,8,6, 4 and 2 mm).…”
Section: Study Design -Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation